2012
DOI: 10.1007/s11745-012-3654-5
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Peroxidation: Lack of Effect of Fatty Acid Pairing

Abstract: Phospholipids where both fatty acids are polyunsaturated are very rare. Most organisms prefer to couple their polyunsaturated fatty acids (PUFA) with either a saturated (SAT) or a monounsaturated (MUFA) fatty acid. This study examined if these natural couplings are there to protect PUFA from themselves. Specifically, does the coupling of PUFA to SAT or MUFA reduce the potential for increased rates of peroxidation by shrouding these highly peroxidisable fatty acids with less peroxidisable fatty acids? The influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It has previously been suggested that polyunsaturated fatty acids might increase intracellular oxidative stress, including lipid peroxidation . Because AEA is very similar to AA (arachidonic acid) in its chemical structure, we postulated that it might affect cell viability by increasing intracellular ROS.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It has previously been suggested that polyunsaturated fatty acids might increase intracellular oxidative stress, including lipid peroxidation . Because AEA is very similar to AA (arachidonic acid) in its chemical structure, we postulated that it might affect cell viability by increasing intracellular ROS.…”
Section: Resultsmentioning
confidence: 94%
“…It has previously been suggested that polyunsaturated fatty acids might increase intracellular oxidative stress, including lipid peroxidation. 18,19 Because AEA is very similar to AA (arachidonic acid) in its chemical structure, we postulated that it might affect cell viability by increasing intracellular ROS. We observed significantly higher production of ROS ( Figure 5A) and 8-isoprostanes (prostaglandin-like compounds formed from the free radicalcatalyzed peroxidation of fatty acids; Figure 5B) in the case of AEA than 2-AG and AA.…”
Section: Anandamide Increased the Production Of Reactive Oxygen Specimentioning
confidence: 99%
“…Moreover, the relative peroxidizabilities of free fatty acids may not always be relevant to how they act as acyl groups when attached to larger molecules (Cosgrove et al, 1987;Kubo et al, 2005;Norris et al, 2012;Wijesundera et al, 2008;Zerouga et al, 1995). For instance, phospholipids containing two DHA groups were peroxidized at the similar rates or sometimes a lower rate than phospholipids containing a DHA and a palmitic acyl group when put into liposomes composed of phospholipids with saturated fatty acyl groups, contrary to what would be predicted based on the peroxidizability indexes (Norris et al, 2012). Additionally, phosphatidylethanolamine with DHA appears to have protective effects against peroxidative damage when it is positioned in the outer leaflet of liposomes (Kubo et al, 2005).…”
Section: Potentially Inaccurate Estimates: Maximum Lifespan and Peroxmentioning
confidence: 99%
“…Beside the precise PL composition, the PUFA distribution on the glycerol backbone of PL was worth knowing because the sn ‐2 position is likely to be implied in the increasing resistance of PL towards oxidation. This issue need further investigation due to controversial results in the literature . Moreover, further studies will be undertaken to quantify the amount of PL classes for the different cakes in order to fully characterize the PL fraction.…”
Section: Discussionmentioning
confidence: 99%